2020
DOI: 10.18632/aging.102672
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29b-3p promotes particulate matter-induced inflammatory responses by regulating the C1QTNF6/AMPK pathway

Abstract: Inflammatory responses are considered to be the critical mechanism underlying particulate matter (PM)induced development and exacerbation of chronic respiratory diseases. MiR-29b-3p has been found to participate in various biological processes, but its role in PM-induced inflammatory responses was previously unknown. Here, we constructed a miRNA PCR array to find that miR-29b-3p was the most highly expressed in human bronchial epithelial cells (HBECs) exposed to PM. MiR-29b-3p promoted PM-induced pro-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…However, miR-29-3p was thought to promote IL-8 and other cytokine expression in a mouse respiratory disease model [41]. However, miR-31 is also associated with TNS1 downregulation, an enhancer of immune infiltration [23].…”
Section: Sars-cov-2 Infected Nhbe Cells (Bronchial)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, miR-29-3p was thought to promote IL-8 and other cytokine expression in a mouse respiratory disease model [41]. However, miR-31 is also associated with TNS1 downregulation, an enhancer of immune infiltration [23].…”
Section: Sars-cov-2 Infected Nhbe Cells (Bronchial)mentioning
confidence: 99%
“…The study does not explore the contextual mechanism of these miRNAs, but they may be further evidence of the unique infection and CSS-related inflammation that is severe COVID-19, given that existing literature implicates these two miRNAs in both pro-inflammatory and anti-inflammatory function, depending on disease. For instance, in a model of particulate matter-induced respiratory disease (therefore not infection-related), miR-29-3p was in fact found to promote IL-8 and other pro-inflammatory cytokine expression [ 41 ], despite being inversely correlated with IL-8 in COVID-19 [ 37 ]. Conversely, in an infection event, another study linked miR-29b-3p upregulation with reduced MAPK activation and NF-κB signalling after LPS stimulation in neonatal rat cardiomyocytes, reducing inflammatory damage in this model of sepsis-induced cardiac arrest [ 40 ].…”
Section: Ncrnas In Immune Cell Recruitment and Differentiation A Precursor To Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Complement C1q Tumor Necrosis factor-related Protein 6 ( C1QTNF6 ) is an inflammation-related gene, which has been preliminarily described to be related to the biological characteristics of tumors ( Wang et al, 2020 ). Zhang et al found that C1QTNF6 regulates proliferation and apoptosis of non-small cell lung cancer (NSCLC) ( Zhang and Feng, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-29b-3p expression is upregulated in patients with congenital heart disease and miR-29b-3p silencing promotes cardiomyocyte proliferation via targeting NOTCH2 ( 17 ). miR-29b-3p contributes to the inflammatory response of human bronchial epithelial cells stimulated by particulate matter by suppressing the AMPK pathway ( 18 ). miR-29b-3p promotes the apoptosis of retinal microvascular endothelial cells via downregulating sirtuin-1 in an in vitro model of diabetic retinopathy ( 19 ).…”
Section: Introductionmentioning
confidence: 99%